THE EFFECTS OF THE COVID-19 PANDEMIC ON PATIENTS WITH MULTIPLE SCLEROSIS IN SULAIMANI CITY, IRAQI KURDISTAN REGION: A HOSPITAL-BASED CROSSSECTIONAL STUDY - Sabir, Kanar Ibrahim; Al-Bajalan, Sarwer Jamal; Kurmanji, Mohammad Tahir (Journal of Sulaimani Medical College, 2024)
Background Multiple sclerosis (MS) is a chronic autoimmune disease that affects the central nervous system and has a wide range of symptoms. Both coronavirus disease 2019 (COVID-19) and MS are known to trigger autoimmune infl ammatory changes. It is not surprising that each is affected by the other. Objectives To evaluate the effects of the COVID-19 pandemic on MS patients, particularly the relapse severity and frequency, the history of vaccination, and any related complications. Patients & Methods A cross-sectional study was performed on 205 MS patients registered in the Sulaimani MS Clinic at Shar Teaching Hospital from March 2021 to March 2022. Detailed demographic features, MS relapses, and symptoms one year before and during the COVID-19 infection were recorded. The rate of affection and symptomatology of COVID-19, the rate of vaccination, and compliance with MS disease-modifying therapies were assessed. Results The mean age was (40.8±11.2 years), and the male-to-female ratio was (0.5:1). The frequency of COVID-19 infection among MS patients was (37.6%). Medical comorbidity was found in 15.1% of MS patients, but it did not impact COVID-19 affl iction (p-value of 0.495). A signifi cant proportion of patients stopped their diseasemodifying therapies during COVID-19 (16.1%). The associations between medical history and MS treatments with COVID-19 infection were insignifi cant. Only a few symptoms increased by 0.5%; other symptoms did not change. COVID-19 signifi cantly led to the stoppage of MS treatment, with a signifi cant association. The demographic characteristics of the MS patients were insignifi cantly associated with COVID-19. The majority of patients (24.9%) were on Betaferon. The vaccination program was completed in (37.1%) patients with no signifi cant post-vaccination change. Conclusions The frequency of COVID-19 infection among MS patients was 37.6%. The associations between demographic characteristics, MS disease-modifying therapies, and COVID-19 infection were insignifi cant. The association of vaccination with COVID-19 infection was signifi cant, but no changes were experienced after vaccination.
Keywords: Coronavirus; COVID-19; multiple sclerosis (MS); severe acute respiratory syndrome coronavirus type-2 (SARS-CoV-2); Sulaimani